2022
DOI: 10.1073/pnas.2114303119
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of toxicity of the mutant huntingtin protein by its interacting compound, desonide

Abstract: Significance Classical drug discovery identifies inhibitors that block the activities of pathogenic proteins. This typically relies on a measurable biochemical readout and accessible binding sites whose occupancy influences the activity of the target protein. These requirements make many pathogenic proteins “undruggable.” Here, we report a strategy to target these undruggable proteins: screening for compounds that directly bind to the undruggable target and rescue disease-relevant phenotypes. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Furthermore, polypharmacology is not only a feature of individual molecules but also entire compound classes. Very prominent examples are steranes or sterane-like molecules, such as azadiradione [ 28 ], beclomethasone [ 39 ], betamethasone [ 39 ], budesonide [ 39 ], carbenoxolone [ 117 ], celastrol [ 38 ], deacetoxy-7-oxogedunin [ 29 ], deacetylgedunin [ 29 ], deoxygedunin [ 29 ], desonide [ 118 ], 18β-glycyrrhetinic acid [ 117 ], gugglesterone [ 39 ], hydrocortisone [ 39 ] olesoxime [ 16 , 119 ], ouabain [ 117 ], prednisolone [ 39 ], proscillaridin A [ 117 ], triamcinolone [ 39 ], ursodeoxycholic acid (ursodiol) [ 14 ], and withaferin A [ 120 ]. These address several target categories, such as mitochondrial systems and novel, diverse targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, polypharmacology is not only a feature of individual molecules but also entire compound classes. Very prominent examples are steranes or sterane-like molecules, such as azadiradione [ 28 ], beclomethasone [ 39 ], betamethasone [ 39 ], budesonide [ 39 ], carbenoxolone [ 117 ], celastrol [ 38 ], deacetoxy-7-oxogedunin [ 29 ], deacetylgedunin [ 29 ], deoxygedunin [ 29 ], desonide [ 118 ], 18β-glycyrrhetinic acid [ 117 ], gugglesterone [ 39 ], hydrocortisone [ 39 ] olesoxime [ 16 , 119 ], ouabain [ 117 ], prednisolone [ 39 ], proscillaridin A [ 117 ], triamcinolone [ 39 ], ursodeoxycholic acid (ursodiol) [ 14 ], and withaferin A [ 120 ]. These address several target categories, such as mitochondrial systems and novel, diverse targets.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the positive effects of steranes and sterane-like molecules on HD pathology in various HD models [ 14 , 16 , 28 , 29 , 38 , 39 , 117 , 118 , 119 , 120 ], particularly the cholesterol (and phospholipid) transporters ABCA1 (and potentially its functional compensatory counterpart ABCA7 [ 164 , 165 ]) gain relevance in the pathogenesis of HD and potential therapeutic and diagnostic interventions, which warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…101,102 Previous experiments have indicated that the binding sites of both molecules are at the N-terminal domain, where CLR01 destructs the N-terminal amphiphilicity 101 and desonide enhances the polyubiquitination of K 6 . 102 In the case of ispinesib, we have also observed that the binding sites contain residues outside of the polyQ tract, i.e. , not only T 3 in the N-terminal domain but also L 113 in the C-terminal domain.…”
Section: Resultsmentioning
confidence: 99%
“…Besides ispinesib, two other molecules, CLR01 and desonide, are also able to inhibit the aggregation of pathogenic Httexon-1. 101,102 Previous experiments have indicated that the binding sites of both molecules are at the N-terminal domain, where CLR01 destructs the N-terminal amphiphilicity 101 and desonide enhances the polyubiquitination of K 6 . 102 In the case of ispinesib, we have also observed that the binding sites contain residues outside of the polyQ tract, i.e., not only T 3 in the N-terminal domain but also L 113 in the C-terminal domain.…”
Section: Distinct Binding Mechanisms In Q72 and Q25mentioning
confidence: 99%
See 1 more Smart Citation